On the role of communication and management engagement for acquisition success: A study of Israeli startups - Jan Polowczyk; Ofer Zaks; Piotr Trąpczyński (International Entrepreneurship Review, 2021)
Objective: The aim of this paper is to shed light on the effects of communication and management engagement on start-up acquisition success.